2004
DOI: 10.1088/0963-0252/13/4/005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a dielectric barrier discharge operating in an open reactor with flowing helium

Abstract: A dielectric barrier discharge (DBD) generated by flowing helium between the parallel-plate electrodes of an open air reactor has been characterized using time resolved optical and electrical measurements. A sinusoidal voltage of up to 5 kV (peak to peak) of frequencies from 3 to 50 kHz has been applied to the discharge electrodes. The helium flow rate is varied up to 10 litre min −1 . The adjustment of flow rate allows the creation of uniform DBDs with optimized input power equal to 120 ± 10 mW cm −3 . At flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
113
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 23 publications
13
113
0
Order By: Relevance
“…Temperature measurements carried out in this study in the effluent region *10 mm from the nozzle resulted in a lower thermal temperature of 293 K. This indicates that the plasma activated species are rapidly cooled in the expanding effluent region to such a degree that allows heat sensitive treatment of polymeric and composite materials and many medical applications [38]. It has been shown that the temporal dependence of discharges and the presence of metastables can influence the time averaged rotational temperature of the molecules [34]. Here for example a similar analysis of the (m = 0?1) emission band of molecular nitrogen at k = 357 nm as well as of the (0 ?…”
Section: Rotational Temperaturesmentioning
confidence: 71%
See 2 more Smart Citations
“…Temperature measurements carried out in this study in the effluent region *10 mm from the nozzle resulted in a lower thermal temperature of 293 K. This indicates that the plasma activated species are rapidly cooled in the expanding effluent region to such a degree that allows heat sensitive treatment of polymeric and composite materials and many medical applications [38]. It has been shown that the temporal dependence of discharges and the presence of metastables can influence the time averaged rotational temperature of the molecules [34]. Here for example a similar analysis of the (m = 0?1) emission band of molecular nitrogen at k = 357 nm as well as of the (0 ?…”
Section: Rotational Temperaturesmentioning
confidence: 71%
“…When the discharge power and helium flow is increased the discharge expands into the volume of the quartz tube where it becomes more luminous. The time dependent electrical signals indicate that the constricted or localized plasma is corona/filamentary-like with chaotic temporal structure and that the volume plasma is more quiescent and glow-like occurring once each cycle of the applied voltage when the voltage is positive [34]. The computed peak current density for these discharges range from 10 to 75 mA/cm 2 ; this would indicate the discharge is more likely to be filamentary in the localized mode rather than corona which generally have a current density of the order of lA/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For displaying the waveform of the discharge current on the oscilloscope the reactor down plate was grounded through a current measurement resistor of 1200Ω. A simple and reliable method for obtaining the consumed power is using the discharge Lissajous figures, obtained when plotting transported electric charge Q through the discharge as a function of the applied periodical voltage [9,10]. Experimentally, the charge Q is delivered from the voltage drop across a measuring serial capacitor of 0.91µF.…”
Section: Methodsmentioning
confidence: 99%
“…18 To support this further, we considered the He͑3 3 S 1 → 2 3 P 0,1,2 ͒ transition at 706.5 nm which is known to be a good indication of the presence of either electrons with energies above 2.9 eV or He 2 + ͑v ‫ء‬ ͒ and low energy electrons. 19 As the frequency increases from 10 to 80 MHz, the 706.5 nm emission intensity increases by 19-fold, indicating an increase in either electron density or electron temperature, both of which are likely to enhance application efficiency. Also worth noting is the similarity in the increase in the maximum power density and in the emission intensity at 706.5 nm.…”
mentioning
confidence: 99%